Global survey of current barriers to project risk management and their impact on projects - Masár, Matej; Hudáková, Mária; Melkovič, Tomáš; Šuleř, Petr (Journal of Business Economics and Management, 2022)
The main goal of this contribution is to assess and evaluate the degree to which project risk management is currently applied in companies at the global level based on empirical research. More specifically, it aims to assess the degree to which project risk management is applied during the initiation and planning phases of projects. In 2019, global empirical research was carried out in 31 countries in Europe, Africa, Australia, Asia, and America. In total, 1,143 project managers participated. The research was conducted on the basis of an online questionnaire survey. For the quantitative data analysis, mathematical and statistical data assessment tests were used to process the obtained data. Although the results reveal an increasing interest among top managers in the application of project risk management, they also show that project managers do not apply risk management to every project. The results of this contribution are applicable to managers and project managers in enterprises around the world, especially in European countries. Results highlighted the importance of project risk management and enhancing its application. In this way, managers can potentially reduce the time and financial losses that may affect the successful project realization.